Translations in the area of social insurance scheme - Romanowska, Dominika (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The subject of the present article is the translation between Polish and Italian social security systems. In the first part the reader shall be informed about how each system has been formed throughout the history. Different formation of systems resulted in different structures of the institutions in Poland and in Italy. The second part briefly presents those structures – Polish ZUS and Italian INPS and INAIL – and lists the responsibilities of each of them which helps to spot the differences. The ultimate, essential part, demonstrates difficulties faced by translators specialized in the field of social insurance. Several terms represented in one language can have various formulations in the other one according to the context in which they occur. There are also terms that have non-equivalent in the other system. The most common ones are listed in the chart in order to present every possible translation of the potentially problematic lemmas.